Structure, function and development of the digestive system in malacostracan crustaceans and adaptation to different lifestyles - Štrus, Jasna; Vogt, Günter (Cell & tissue research, 2019)
The digestive system of the malacostracan crustaceans, namely the decapods, isopods, amphipods and mysids, is among the most complex organ systems of the animal kingdom serving multiple functions such as food processing, absorption and storage of nutrients, synthesis of digestive enzymes and blood proteins, detoxification of xenobiotics and osmoregulation. It is rather well investigated compared to other invertebrates because the Malacostraca include many ecological keystone species and food items for humans. The Decapoda and Peracarida share food processing with chewing and filtering structures of the stomach but differ with respect to morphology and ultrastructure of the digestive glands. In the Peracarida, the digestive glands are composed of few, relatively large lateral caeca, whereas in the Decapoda, hundreds to thousands of blindly ending tubules form a voluminous hepatopancreas. Morphogenesis and onset of functionality of the digestive system strongly depend on the mode of development. The digestive system is early developed in species with feeding planktonic larvae and appears late in species with direct lecithotrophic development. Some structures of the digestive system like the stomach ossicles are rather constant in higher taxa and are of taxonomic value, whereas others like the chewing structures are to some degree adapted to the feeding strategy. The nutrient absorbing and storing cells of the digestive glands show considerable ultrastructural variation during moult cycle, vitellogenesis and starvation. Some of the various functions of the digestive system are already assigned to specific sections of the digestive tract and cell types, but others still await precise localization.